Clinical Features and Incidence of Musculoskeletal Disorders in Children With Juvenile Idiopathic Arthritis - Ikrom qizi, Yarashova Shakhlo (American Journal of Bioscience and Clinical Integrity, 2026)
We studied the clinical features of musculoskeletal lesions in 56 children with juvenile idiopathic arthritis (JIA). We determined the nature of histological changes in the synovial membrane, articular cartilage, and subchondral bone depending on the clinical form of the disease and the duration of the inflammatory process.